A New Trajectory Optimizing Method Using Input Shaping Principles - Pu Zhao; Yunfei Zhou; Rougang Zhou (Shock and Vibration)
Input shaping is an efficient control technique which has motivated a great number of contributions in recent years. Such a technique generates command signals that can manoeuvre flexible structures without exciting their vibration modes. This paper introduces a new trajectory optimizing method based on input-shaping principles. The main characteristic of this method in comparison with traditional input-shaping technique is the generating process of final trajectory. By adding reversion and postprocessing procedures before input shapers, time-delay and most of the trajectory deviation can be removed. The improvement of the proposed method compared with a traditional method is evaluated by simulations. It will be shown that the proposed method leads to no time-delay and highly decreased trajectory deviation and little change of robustness.